EVALUATION OF THE VIABILITY OF TARIFFS BASED ON TRANSPORTATION EXPENSES FOR CATAMARAN RIVER SERVICES ON THE PARANGLOE - LAKKANG ROUTE - Muh Yusril Syam; Ainun Chandra Puspa Nigrum (Journal of Marine-Earth Science and Technology, 2025)
Establishing ship fares necessitates a thorough examination because it encompasses multiple cost factors, with fuel being the primary expense. For operators, it is crucial to determine fares that not only account for operational expenses but are also competitive and accessible for users of the service. This research investigates the viability of river transport fares using catamaran vessels on the Parangloe–Lakkang route, which can accommodate 12 passengers and 10 motorcycles, with a maximum of 8 vessels in operation. The aim of this research is to assess the minimum fare needed for the vessels to function sustainably by employing the Required Freight Rate (RFR) method, alongside evaluating passengers' ability and willingness to pay through the Ability to Pay (ATP) and Willingness to Pay (WTP) methodologies. The analysis reveals that the lowest minimum fare for passengers is Rp1.910/trip for vessel 3, while vessel 8 has the highest minimum fare at Rp2.442/trip. The ATP for passengers has been noted at Rp2.893/trip, whereas the WTP is recorded at Rp2.000/trip. These findings imply that the RFR fare falls between the WTP and ATP figures, indicating it is within a suitable range for fare policy. This result is significant as it provides a foundation for establishing sustainable fares and promotes enhancements in the quality of river transport services to ensure they are safer and more enjoyable for passengers.